PREDICTION OF MISSING VALUES USING KNOWLEDGE GRAPH - BOURAS et BELHADJAMI, AMINA BOCHRA et MESSAOUD (Faculty of mathematics and informatics DEPARTMENT OF COMPUTER SCIENCE -, 2020)
After the spread of the term knowledge graph in the recent years and the definition of its concept and how to represent it, it was used by many companies for different purposes. As well, KG has relation with some domains and it is under development. The aim of this dissertation is to verify the possibility of applying the knowledge graph in the data mining domain in order to solve the problem of missing values in the database. Therefore, KG becomes a prediction technique which can be developed and used in this domain.
Keywords: Knowledge graph, missing values, prediction techniques, Database.